The Influence of Work Facilities and Internal Communication on the Performance of Civil Servants Through Motivation at the Education Office and Culture of Muaro Jambi Regency - Jasrianto, Jasrianto; Zahari, M.; Hapsara, Osrita (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study evaluates and analyzes the impact of work facilities and internal communication on civil servant performance, with work motivation as a mediating variable, at the Education and Culture Office of Muaro Jambi Regency. Using both descriptive and verification methods, the research involved 62 employees from the office and employed the Partial Least Squares (PLS) method for analysis. The results from the questionnaire indicated that work facilities had a total score of 2859, classified as good, while internal communication scored 2836, also in the good range. Work motivation was rated at 3080, placing it in the high category, and employee performance scored 3099, which is similarly high. The findings show that work facilities have significant impact on motivation. Internal communication also positively and significantly influences motivation. Additionally, both work facilities and internal communication have significant effect on employee performance. Motivation is demonstrated to positively and significantly affect employee performance. Moreover, work facilities and internal communication both positively and significantly impact employee performance through the mediation of motivation at the Muaro Jambi Regency Education and Culture Office.